Phonological Analysis in Delivering Stories through Video Recording - Purnami, Ni Made Ayu; Junipisa, Ni Made Ernila; Wedayanthi, Luh Made Dwi (Linguistics and ELT Journal, 2023)
Postulating the language as means of communication playing crucial role in our daily lives is truly indisputable. A lot of problems occurred in the field of phonology by the students in delivering their speaking performance. This research is intended to analyze the phonological error in the second semester students in performing stories in the form of speaking. The kind of this research is classified as qualitative research which focuses on analyzing students’ utterances, particularly in terms of English phonology. In this study, the data were collected in the form of video-recorded speaking performance and written transcription by the subjects of the research. Furthermore, after a careful and detailed analyzing process by the researcher, it is concluded that most students made several phonological errors in pronouncing some English words. The result of the study showed that diversity of language skills and components particularly pronunciation, fluency, and accuracy is dominantly due to the previous educational background, students’ motivation in learning, the intensity of students’ exercise, students’ current efforts in learning English, and having a grit. By having a grit, the students have passion and perseverance to train themselves in learning English and practicing the English skills for long-term.